STRATEGY OF EDUCATION QUALITY IMPROVEMENT ON SENIOR HIGH SCHOOL ARGOPURO PANTI - Al-Hamzah, Syaeful; Firdaus, Muhammad; Zainollah (MBA : Journal of Management and Business Aplication, 2021)
Quality of education is one of the central isue of national education among other isues such as equlization, relevance and educational management eficiencies. SMA Argopuro Panti is still faced with several obstacles that affect the quality of education, which regard to the background of students and their families, support of educational resources, teachers qualification, and low community participation. This research aims to obtain information about the policies underlying the school-based education quality improvement program, and how the school stakeholders understanding of the policy and to analyze information about alternative strategies for improving the quality of schoole-based education, regarding to the education program in SMA Argopuro Panti Jember. Informants in this study are founders of foundations, school committee members, and teacher, research subjects are relatively few and selected according to the research objects. In this study, collection uses snowball sampling techniques. Data analysis method uses SWOT analysis method. Based on the results of the analysis it is known that SMA Argopuro Panti is in a very favorable situation, it should able to compete because according to data analysis this school already has the strengthand opportuintyto improve its quality and dare to compete with other schools. The strategy applied in this condition is to support an aggressive growth policy growth oriented strategy. Keywords : Strategy, Development, Quality of Education